Passive Design, Urban-Rural Architectural Morphology for Subtropics - Khalid, Asma (European Journal of Sustainable Development, 2020)
Built environment is a function of man-made setting, surroundings, conditions which is the center of human activity in architectural places. The integration of nature into the built environment determines the urban or the rural form of settlements. The present research aims to specify architectural morphology of sub-tropical region through a case analysis of the situation in Pakistan. The field study analyses the existing housing stock in Pakistan, in urban settings and as a result of vernacular traditions in the villages. The paper identifies the regional characteristic behaviour of highland, lowland, coastal and arid region. It gives an overview of the current urban housing situation in Pakistan. It discusses the type of housing unit, the occupant behaviour, lifestyle of the people, It also identifies the pattern of energy used within the residential buildings of Pakistan. The architectural planning in urban and rural regions, their long term passive design techniques to cope with the climate challenges of a particular area have been discussed in detail. The paper recommend some contextual and adapted passive features of vernacular architecture in urban houses. Keywords: Architectural-morphology, Urban, Housing, Vernacular, Passive Design, Built Environment